DISTRIBUTION MAPPING OF GLYPHOSATE-RESISTANT Eleusine indica IN SERDANG BEDAGAI REGENCY - Koko Tampubolon; Edison Purba; Mohammad Basyuni; Diana Sofia Hanafiah (Jurnal Natural, 2018)
The presence of Eleusine indica from oil palm plantations in Serdang Bedagai Regency has never been overall reported glyphosate-resistant. This study aims to distribution mapping and resistance classification of E. indica population to glyphosate herbicide of oil palm plantations in Serdang Bedagai Regency. This research was conducted on Weed Research Center Land in Faculty of Agriculture, Universitas Sumatera Utara in October 2016 to August 2017. This research used glyphosate herbicide with the recommended dose at 720 g ai ha-1 and three replications. Population ESU0 (from Politeknik Negeri Medan Ball Field) as a comparison. Data analysis using IBM SPSS Statistics 20 software. The results showed there E. indica population classified as glyphosate-resistant amount 89.36% (42 population), classified as glyphosate-resistant moderate amount 10,64% (5 population) and there is no population glyphosate-susceptible on oil palm plantations in Serdang Bedagai Regency of recommended dose at 720 g ai ha-1.